Sosio-Cultural Analysis of Divorce Legislation a Comparative Study Between Indonesia and United Kingdom - Fakhriyah Tri Astuti; Setiyawan bin Gunardi; Erni Erni Dewi Riyanti (Department of Ahwal Syakhshiyah, Faculty of Islamic Studies, Universitas Islam Indonesia, 2024)
Non-Indexed Publication